Where is Vocational Education Heading? Unpacking Two Decades of Global Knowledge Dynamics and Policy Relevance - Wulaningrum, Tri; Afnia, Pangestika Nur; Setiawan, Risky (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – As digital disruption and global inequalities reshape the future of work, vocational education is increasingly recognized as essential for skills development and social mobility. However, the field remains marked by thematic fragmentation—between traditional foci such as curriculum and pedagogy and emerging priorities like digitalization, equity, and learner well-being—and significant geographical imbalance, with research output dominated by a few high-income countries. This study maps the intellectual and policy landscape of vocational education research (2000–2024) to clarify its alignment with urgent global challenges.Method – A total of 11,781 Scopus-indexed articles was analyzed using bibliometric tools in R, including keyword co-occurrence, thematic mapping, and international collaboration network analysis to reveal dominant clusters and neglected themes. Findings – Research in vocational education is anchored in curriculum and employability, yet digital skills, gender inclusion, and mental health remain underexplored. Publication is concentrated in Australia, the US, Germany, and China, reinforcing North–South disparities and limiting global integration. While interest in innovation is rising, persistent conceptual fragmentation still hinders policy impact. Research Implications – Policymakers should move beyond rhetoric to embed digital skills, equity, and well-being in policy and curricula. Future research needs to address underrepresented issues and regions, foster cross-country collaboration, and better translate evidence into practice. The focus on English-language, Scopus-indexed articles may exclude some regional scholarship.